Obesity as a multidimensional problem in the health care system - literature review - Grzybowski, Jakub; Walczak, Patrycja; Hordejuk, Michalina; Marczak, Aleksandra; Hyjek, Michał; Szymkiewicz, Karolina; Walczak, Klaudia (Quality in Sport, 2023)
Awareness among medical professionals and patients about the impact of obesity on health is currently at a good level. Medical recommendations often include the recommendation of weight reduction, and there are increasing numbers of dieticians on wards educating patients about a healthy diet and physical activity. Special programs are also being developed to provide pharmacological and surgical treatment for obesity. New drugs that reduce body fat are becoming available. Unfortunately, as statistics show, the problem is still global and the number of obese people is increasing over the years. Currently, there is a huge emphasis on treating and reversing the effects of obesity, rather than preventing it. Scientific and technological advances are lagging behind in the face of the challenges posed by the large obese population. In this work, we present the radiological, anesthesiological and surgical problems and limitations associated with obesity, which may not be obvious to those who do not deal with obese patients on a daily basis as well as the patients themselves.